Effect of carbon addition on the passivity of hypoeutectic high chromium cast irons. Issue 1 (22nd December 2022) - Lee, Jun-Seob; Lee, Jun-Hyeong; Oh, Jun-Seok; Kang, Sung; Baek, Seung-Hoon; Ahn, Jee Hyuk; Han, Seung Zeon; Lee, Je-Hyun
Abstract : The effect of adding C on the passivity of hypoeutectic high chromium cast iron (HCCI) was investigated in a pH 8.4 boric-borate buffer solution. Abstract : The effect of adding C on the passivity of hypoeutectic high chromium cast iron (HCCI) was investigated in a pH 8.4 boric–borate buffer solution. The microstructure of HCCI is composed of austenite and carbide phases, whose fractions and chemical compositions are influenced by the amount of C added. Electrochemical and surface analyses revealed that the addition of C in the HCCI increased the defect densities in the n-type and p-type semiconductive oxide layers on the austenite and carbide phases, respectively.